State of California Secretary of State Certificate of Delegate - March Fong Eu:::::: (1976)
This document is an official Certificate of Delegate issued by the State of California and signed by Secretary of State March Fong Eu. It certifies that Jane Tolmach was selected as a delegate to represent California at the 1976 Democratic National Convention. The certificate bears the state seal and formal language attesting to the appointment in July 1976.